2021
DOI: 10.1101/2021.07.18.452791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ensemble encoding of conditioned fear by prefrontal somatostatin interneurons

Abstract: Neurons preferentially activated by learning have been ascribed the unique potential to encode memory. However, it remains unclear which genetically-defined cell types are recruited as part of such an ensemble, or what role discrete subpopulations play in behavior. Here we show that fear conditioning activates a heterogeneous neural ensemble in the medial prefrontal cortex (mPFC), comprised to a large degree of GABAergic interneurons immunoreactive for somatostatin (SST-INs). Using an intersectional genetic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Furthermore, recent research has shown that cortical spike timing dependent plasticity of PV+ interneuron-mediated inhibition contributes to auditory map remodeling (Vickers et al, 2018). Similarly, prefrontal SST+ interneurons have been reported to encode fear memory (Cummings and Clem, 2020;Cummings et al, 2022). Although we did not thoroughly investigate the mechanisms underlying fear memory-mediated long-term inhibitory synaptic plasticity, our results indicate that the frequency of mIPSCs were potentiated by fear memory, predominantly in PKC-δ(+) neurons.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, recent research has shown that cortical spike timing dependent plasticity of PV+ interneuron-mediated inhibition contributes to auditory map remodeling (Vickers et al, 2018). Similarly, prefrontal SST+ interneurons have been reported to encode fear memory (Cummings and Clem, 2020;Cummings et al, 2022). Although we did not thoroughly investigate the mechanisms underlying fear memory-mediated long-term inhibitory synaptic plasticity, our results indicate that the frequency of mIPSCs were potentiated by fear memory, predominantly in PKC-δ(+) neurons.…”
Section: Discussionmentioning
confidence: 61%
“…The role of inhibitory engrams is currently debated (Josselyn and Tonegawa, 2020). So far, engrams formed by inhibitory neurons have been mostly studied in circuits expressing both glutamatergic and GABAergic cells (Cummings and Clem, 2020;Cummings et al, 2022). In this context, GABAergic engram neurons have been proposed to play a role in keeping the balance or controlling the extension of glutamatergic excitatory engrams (Barron et al, 2017;Josselyn and Tonegawa, 2020;Rao-Ruiz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3E, H). Limited Oprm1 was found in somatostatin (Sst) and vasoactive intestinal polypeptide (Vip) GABAergic interneurons (79,80). To localize putative nociceptive celltypes, we used two measures of noxious-evoked IEGs-a weighted distribution 'activity score' and IEG density mapping with Nebulosa of n=25 IEGs (Fig.…”
Section: Cingulate Cartography Of Opioidergic and Nociceptive Cell-typesmentioning
confidence: 99%
“…In an assay stimulating cultured neurons, E-SARE has demonstrated higher reporter expression levels and a dynamic range compared to the c-Fos promoter ( Kawashima et al, 2013 ). E-SARE was used to label activated neurons in cortex ( Kawashima et al, 2013 ; Cummings et al, 2021 ) and hippocampus ( Attardo et al, 2018 ).…”
Section: Advances In Activity-dependent Gene Expressing Systemsmentioning
confidence: 99%